Performance Analysis of Wave Energy Harvesting System with Piezoelectric Element - Koca, Ahmet; Erdogan, Kubra (Springer International Publishing Ag, 2018)
Wave energy harvesting systems capture power from the sea or ocean waves. Piezoelectric elements are materials that can create electricity when subjected to a mechanical stress. In this study, wave energy harvesting system with piezoelectric element is used to generate power. For this aim, a wave tank with wavemaker was built in laboratory condition. Wavemaker generates sinusoidal twin waves with 4 cm height per second. An obstacle with piezoelectric element is placed in the tank. The parameters of the experimental study are obstacle position and piezoelectric element angle with water level. It is found that the position and angle of the piezoelectric element is very important to generate power for the wave harvesting systems.
12th International Conference on Mechatronics -- SEP 06-08, 2017 -- Brno, CZECH REPUBLIC
Keywords: Piezoelectric; Wave harvesting; Wave tank